Outcome of advanced lung cancer with central airway obstruction versus without central airway obstruction. Issue 2 (9th April 2018) - Verma, Akash; Goh, Soon Keng; Tai, Dessmon Y.H.; Kor, Ai Ching; Soo, Chun Ian; Seow, Debra G.F.; Sein, Zin Nge Nge; Samol, Jens; Chopra, Akhil; Abisheganaden, John
Patients with central airway obstruction (CAO) from advanced lung cancer present with significant morbidity and are assumed to have lower survival. Hence, they are offered only palliative support. We asked if patients who have advanced lung cancer with CAO (recanalised and treated) will behave similarly to those with advanced lung cancer without CAO. This study was a retrospective review of the medical records of the patients managed for advanced lung cancer during 2010 and 2015 at our institution. 85 patients were studied. Median survival and 1-, 2- and 5-year survival were 5.8 months, 30.3%, 11.7% and 2.3% versus 9.3 months, 35.7%, 9.6% and 4.7%, respectively, in the CAO and no CAO groups (p=0.30). More patients presented with respiratory failure (15 (35%) versus none; p=0.0001) and required assisted mechanical ventilation (10 (23.3%) versus none; p=0.001) in the CAO group compared with the no CAO group. Fewer patients received chemotherapy in the CAO group (11 (25.5%)) compared with the no CAO group (23 (54.7%); p=0.008). There was no difference in survival among patients with advanced lung cancer whether they presented with CAO or without CAO. Survival was similar to those without CAO in patients with recanalised CAO despite greater morbidity and lesser use of chemotherapy, strongly advocating bronchoscopic recanalisation of CAO. These findings dispel the nihilism associated with such cases. Survival is similar among patients with advanced lung cancer whether they present with CAO or without CAO http://ow.ly/djRE30iDH6V